PELUANG DAN TANTANGAN IMPLEMENTASI ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN PAUD: STUDI FENOMENOLOGI - Imut, Dara; Tana Kimisa, Dwi; Pransiska, Anjelita; chairani, Dema; Fadilah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology, particularly Artificial Intelligence (AI), has created new opportunities to enhance the quality of learning in Early Childhood Education (ECE). This study aims to analyze the opportunities and challenges of implementing Artificial Intelligence in ECE learning through a phenomenological approach. The research employed a qualitative method with research subjects consisting of ECE teachers and principals selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed through stages of data reduction, data presentation, and conclusion drawing. The findings indicate that AI provides opportunities to improve teacher creativity, efficiency in developing learning tools, creation of educational media, and provision of varied play activities. However, AI implementation still faces challenges such as limited digital literacy among teachers, infrastructure readiness, information validity, and ethical aspects of technology use. Teachers address these challenges through self-training, collaboration, and evaluation of AI-generated outputs. This study emphasizes that AI serves as a supporting technology for teacher professionalism, not as a replacement for human interaction in ECE learning